2018
DOI: 10.1016/j.theriogenology.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Insemination extender supplementation with bestatin and EDTA has no effect on rabbit reproductive performance

Abstract: The addition of aminopeptidase inhibitors (AMIs) to rabbit semen extenders could be a solution to decrease the hormone degradation (GnRH) by the aminopeptidases existing in the seminal plasma. Therefore, the quantity of GnRH needed to induce ovulation in doe would be comparable with the amount administered intramuscularly (i.m.). This study was conducted to evaluate the effects of two AMIs (bestatin and EDTA) on rabbit semen quality parameters, β nerve growth factor (β-NGF) degradation and reproductive perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Moreover, reports in humans have found that the b-NGF/TrkA system exerts effects on semen parameters [47,48]. b-NGF levels observed in the SP were similar to those reported in rabbits [9,49] but b-NGF concentration in BP was higher than those described by Maranesi et al [9]. Differences among studies may be explained in terms of different kits and laboratory techniques used.…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, reports in humans have found that the b-NGF/TrkA system exerts effects on semen parameters [47,48]. b-NGF levels observed in the SP were similar to those reported in rabbits [9,49] but b-NGF concentration in BP was higher than those described by Maranesi et al [9]. Differences among studies may be explained in terms of different kits and laboratory techniques used.…”
Section: Discussionsupporting
confidence: 72%
“…However, in more recent studies this neuropeptide has been also identified as an ovulation-inducing factor (OIF) present in the seminal plasma (SP) of some reflex ovulating species such as camelids or rabbits [25]. In rabbits, the neuropeptide and its receptors (TrkA and p75) have been identified in all male and female reproductive tissues (testes, epididymis and accessory glands [610], SP [7, 8, 10, 11], uterus, oviduct and ovary [12–14]). While some studies have suggested a role of β-NGF in the mechanism of ovulation in rabbits [8, 12, 15], evidence of its role as an OIF in this species, as found in camelids, is still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to degradation by aminopeptidases and the low absorption in the vagina mucosa, there is a decrease in the analogues' bioavailability and large doses are required for ovulation induction following vaginal administration. According to a previous work [6], the employment of bestatin and EDTA in the rabbit insemination extenders inhibited part of the seminal aminopeptidase activity without affecting reproductive performance. On the other hand, we have developed CS-DS nanoparticles to entrap the GnRH analogue and a previous in vitro characterization showed that these nanoparticles did not affect rabbit seminal quality [12].…”
Section: Reproductive Performance Of Experimental Extendersmentioning
confidence: 90%
“…CS and DS were dissolved (0.05%) in the Control medium, which consisted in Tris-citric acid-glucose (TCG) supplemented with bestatin 10 µM and EDTA 20 mM [6].…”
Section: Preparation Of Gnrh-loaded Cs-ds Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation